2008
DOI: 10.1590/s0101-20612008000400030
|View full text |Cite
|
Sign up to set email alerts
|

α-, β-caroteno e α-tocoferol em algas marinhas in natura

Abstract: CP 6043, Brasil, sakersil@gmail.com *A quem a correspondência deve ser enviada α-, β-caroteno e α-tocoferol em algas marinhas in natura α-and β-carotene, and α-tocopherol in fresh seaweeds Márcia Barbosa de SOUSA 1 , Kelma Maria dos Santos PIRES 1 , Daniel Barroso de ALENCAR 1 , Alexandre Holanda SAMPAIO 1 , Silvana SAKER-SAMPAIO 1 * IntroduçãoAs macroalgas marinhas constituem um grupo heterogêneo de vegetais encontrados abundantemente em todos os ecossistemas. São fonte de uma grande variedade de compostos be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…β-Carotene is a liposoluble pigment that has pro-vitamin A activity with a long chain of conjugated double bonds produced from an acyclic structure. In the present investigation, the average content of β-carotene (0.52 ± 0.08 mg/100 g DW) is in accordance with that reported by De Sousa ( 46 ), with an average content of 0.4185 ± 0.1559 mg/100 g DW for brown algae Lobophora collected from Brazil. This result was lower than that recorded from the Red Sea (0.47 mg/g DW) ( 29 ) or 0.55 to 4.06 mg/g DW obtained by another work ( 42 ).…”
Section: Resultssupporting
confidence: 92%
“…β-Carotene is a liposoluble pigment that has pro-vitamin A activity with a long chain of conjugated double bonds produced from an acyclic structure. In the present investigation, the average content of β-carotene (0.52 ± 0.08 mg/100 g DW) is in accordance with that reported by De Sousa ( 46 ), with an average content of 0.4185 ± 0.1559 mg/100 g DW for brown algae Lobophora collected from Brazil. This result was lower than that recorded from the Red Sea (0.47 mg/g DW) ( 29 ) or 0.55 to 4.06 mg/g DW obtained by another work ( 42 ).…”
Section: Resultssupporting
confidence: 92%
“…Sousa and others (2008) found the highest contents of α‐tocopherol in green algae when compared to both red and brown algae. Species of Caulerpa showed similar levels of α‐tocopherol to our current data and indicated that daily portions that would be deemed an excellent source or a useful source of vitamin E, would be similar in size as well.…”
Section: Resultsmentioning
confidence: 88%
“…Vegetable oils and their derivatives are the major sources of vitamin E; however, green leafy vegetables, almonds, and grains also are significant producers of this nutrient (Rigotti 2007; Schwartz and others 2008). Some species of marine algae have shown the presence of α‐tocopherol (Sousa and others 2008; Taboada and others 2010). In algae, the variation of the vitamin content and nutritional quality depends on factors such as seasonality, environmental conditions of temperature, salinity, luminosity, freshness, and the method of preservation and processing (industrial or household) (Bernhardt and Schlich 2006; Marinho‐Soriano and others 2006).…”
Section: Introductionmentioning
confidence: 99%
“…α-Tocopherol (24) β-carotene (25), and vitamin A (26) were detected in the methanolic extract of D. delicatula Lamouroux, collected during low tide from Guajiru Beach and Trairi-Ceará (Brazil). α-Tocopherol (24) β-carotene (25), and vitamin A (26) were quantified, and their contents were 26.562 ± 3.627, 0.266 ± 0.198 and 0.044 ± 0.033 µg/g fresh weight, severally [23].…”
Section: Dictyopteris Delicatula Jv Lamouroux 1809mentioning
confidence: 99%